1966
DOI: 10.21273/hortsci.1.3-4.95
|View full text |Cite
|
Sign up to set email alerts
|

Overhead Sprinkler System for Environmental Control and Pesticide Application in Pear Orchards

Abstract: Overhead sprinkler systems are not new to orchard management but have been used almost exclusively for irrigation. However, economic considerations would encourage a modification of this one-purpose system into multi-purpose usage. Potentially, with the correct physical arrangements of pumps, pipes, risers, and nozzles it would be possible not only to irrigate, but to have frost protection and summer environmental and pest control as well. The present paper examines the latter two uses of an overhead sprinkler… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

1972
1972
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Drift results in environmental and natural ecosystem contamination and increases the risk of community exposure to harmful chemicals 21–24 . As an alternative, researchers have been exploring fixed spray systems most recently called solid set canopy delivery systems (SSCDS) 19,25–42 …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Drift results in environmental and natural ecosystem contamination and increases the risk of community exposure to harmful chemicals 21–24 . As an alternative, researchers have been exploring fixed spray systems most recently called solid set canopy delivery systems (SSCDS) 19,25–42 …”
Section: Introductionmentioning
confidence: 99%
“…[21][22][23][24] As an alternative, researchers have been exploring fixed spray systems most recently called solid set canopy delivery systems (SSCDS). 19,[25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42] SSCDS have been extensively tested and optimized for performance in terms of spray deposition and coverage. 19,[31][32][33][34][37][38][39][40][41][42] However, limited information is available on the biological efficacy of such systems for insect and pest management.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…14 C activity in sugars, nonvolatile organic acids and amino acids in leaves and tubers of misted and nonmisted potato plants after 3 hours exposure to 14 CC>2 under high radiation load 2. …”
mentioning
confidence: 99%
“…Overhead sprinkling to reduce heat stress has been studied on cool-season crops such as pears (5), grapes (3) and apples (7). Unrath and Sneed (8) reported that overhead sprinkling re duced fruit temperature of the early apple crop by 5.6°C with a subsequent improvement in quality and yield.…”
mentioning
confidence: 99%